PERUBAHAN STATUS SOSIAL TERHADAP WILAYAH PERINDUSTRIAN DI KOTA SIDOARJO - Sinta, Nuria (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2022)
Humans are dynamic social creatures. As social beings, there are elements that make up the structure as in the structural theory of conflict from Ralph Dahrendorf. The elements that exist in the motives of each community group certainly have different purposes, interests, and goals. This study aims to determine the factors that influence the occurrence of social mobility of the farming population towards industrial areas in Sedati District, Sidoarjo. Data were collected using quantitative methods using questionnaires and analyzed using scoring analysis techniques using the Guttman scale and descriptive analysis. The results of the analysis show that the structural conflicts that occur to the farming population in Sedati District occur due to changes in the physical conditions of the area and changing community structures.